The lack of large investments in green startups by venture capital in Europe: drivers, implications and measures to address the financial gap - Secker, Justin Marek Bert (2021)
Start ups play a critical role in the path to green growth, often exploiting opportunities ignored by incumbents. However, previous research emphasises that green start ups have higher funding needs and tend to have uncertain exit options, high technological risk profiles and regulatory uncertainties that could be critical for conventional venture capitalists (VCs). This creates a severe funding gap caused by the mindset of short-term investors who seek short-term profits to meet performance criteria. This severe lack of funding for green start ups works against all policies towards a green economy, such as the European Green Deal. Therefore, we conducted an exploratory study with VCs. The results of the study con-tribute to the understanding of the drivers, implications and measures against the funding gap. To enable a potential shift towards more funding for green start ups, a collective approach needs to be taken. An interplay of public money and policies that provide direction to sustain the well-being of us all, and private money that builds on that and enables the broad implementation and scalability needed. Furthermore, not only do VCs need to set a new focus, but this needs to be encouraged and demanded by limited partners and investing institutions. Further-more, green start ups need to move away from focusing solely on impact and start integrating profit and impact in a "lock-step" business model. In addition, consumers also need to start consciously investing their capital in things that drive change towards a greener purpose.